C70 Fullerene‐Catalyzed Metal‐Free Photocatalytic ipso‐Hydroxylation of Aryl Boronic Acids: Synthesis of Phenols. Issue 10 (30th March 2018) - Kumar, Inder; Sharma, Ritika; Kumar, Rakesh; Kumar, Rakesh; Sharma, Upendra
Abstract: A metal‐free C70 fullerene‐catalyzed method has been developed for the ipso ‐hydroxylation of aryl and heteroaryl boronic acids to corresponding phenols under photocatalytic conditions. The reaction proceeds under oxygen atmosphere and the mechanistic study revealed that C70 plays a critical role in the generation of reactive oxygen species in the presence of blue light. Reactions in the presence of 18 O‐labelled water and oxygen confirmed the generation of reactive oxygen species from oxygen molecule. Amine used as a reductant could be recovered in the form of imine. The current method is also applicable to the synthesis of aryl ethers in one‐pot two‐step process. Abstract :